Potent Oral Hypoglycemic Agents for Microvascular Complication: Sodium-Glucose Cotransporter 2 Inhibitors for Diabetic Retinopathy - Eun Hyung Cho; Se-Jun Park; Seongwook Han; Ji Hun Song; Kihwang Lee; Yoo-Ri Chung (Journal of Diabetes Research)
The purpose of this study was to investigate the effects of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on the progression of diabetic retinopathy (DR) in patients with type 2 diabetes. The medical records of 21 type 2 diabetic patients who used a SGLT2i and 71 patients with sulfonylurea (control) were reviewed retrospectively. The severity of DR was assessed using the Early Treatment Diabetic Retinopathy Study (ETDRS) scale. Fewer patients who used a SGLT2i than control patients with sulfonylurea showed progression of DR based on ETDRS scale (44% versus 14%, P=0.014). Moreover, treatment with a SGLT2i was associated with a significantly lower risk of DR progression (P=0.021), and this effect remained significant after adjusting for the age, duration of diabetes, initial DR grade, and HbA1c level by propensity score matching (P=0.013). Treatment of type 2 diabetic patients with a SGLT2i slowed the progression of DR compared to sulfonylurea, which is independent of its effect on glycemic control. This study provides a foundation for further evaluation of the effect of SGLT2i on the progression of DR.